Social media Use as correlate of reading habits among undergraduates in University of Ibadan, Nigeria (2021)
Social media comprises of websites and applications that enable users to create and share contents or to participate in social networking. Results showed different types of social media. However, it is discovered that majority of undergraduates devote more time to use social media for different activities like chatting, social activities and reading. This study employed descriptive survey research design targeting undergraduates of University of Ibadan in the 2018 / 2019 session which equalled 14,778. Multistage sampling technique with a 10% was used to select 247 undergraduates across six faculties. The questionnaire was the main data collection instrument and data analysed using descriptive statistics of frequency, percentage and correlation analysis. The Statistical package for social Sciences (SPSS) was the Software used for data analysis. The findings of the study, amongst others revealed that respondents used Facebook most (92.7%) and Instagram (78.1%) has the least. The findings showed that respondents used social media mostly to chat with friends (94.3%) and share information (87.4%). On frequency of use, the study revealed that Facebook (x =4.00), and Wikipedia (x =3.26) were frequently used by respondents. Findings also revealed that there was a positive relationship between social media use and reading habits of undergraduates in University of Ibadan (r = .200, n= 247, p (002)<05) The study concludes that social media should be prudently utilised, not only as a means of communication stay among family and friends but must be used reasonably as a rich educational tool. The study recommended that; efforts should be geared by the Institution authorities towards creating enabling environment for reading, as these will enhance development of reading habit and strengthens academic pursuit of students.